Pedagogical Models: Teachers’ Alternative Scenarios to Enhance Students’ Academic Achievement during the Covid-19 Pandemic - Hanni Yukamana (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: An attempt to contain the spread of the Covid-19 Pandemic by closing educational institutions impacted over sixty percent of the world’s student population. School closure induces learning disruption, generates inequities, and greatly influences underprivileged children. The efforts to mitigate the impacts of school closure and to facilitate the continuity of education have become extremely challenging tasks for teachers. Educators are strongly advised to make a rapid transition to remote learning at short notice. They are expected to provide students with meaningful learning experiences, create feasible academic scenarios that fit their respective teaching and learning contexts as well as enhance students’ achievement. However, without proper training and full support from the government, teachers may find shifting the direction of their teaching from the traditional classroom to virtual learning burdensome. Teachers should be provided with adequate skills and knowledge to perform remote learning successfully in order to maintain students’ high levels of academic performance. This paper intends to explore pedagogical models served as alternative scenarios that teachers can devise to boost students’ academic achievement during the pandemic. Keywords: school closure, rapid transition, remote learning, pedagogical models Abstrak: Usaha untuk memutuskan rantai penyebaran Covid-19 dengan menutup institusi pendidikan mempengaruhi lebih dari enam puluh persen populasi siswa di dunia. Penutupan sekolah menyebabkan terjadinya gangguan belajar, ketidakmerataan, dan sangat mempengaruhi anak-anak yang tidak berkemampuan. Usaha untuk mengurangi pengaruh dari penutupan sekolah dan upaya untuk memfasilitasi keberlangsungan pendidikan menjadi tugas yang sangat menantang bagi para guru. Pendidik di perintahkan untuk mengajar secara online tanpa persiapan. Mereka diharapkan bisa menyediakan siswa pengalaman pembelajaran yang bermakna, menciptakan perencanaan pengajaran sesuai dengan karakter sekolah dan siswa masing-masing, untuk meningkatkan prestasi akademik siswa. Akan tetapi, tanpa pelatihan yang memadai dan bantuan dari pemerintah, para pendidik akan mengalami kesulitan untuk beralih ke pembelajaran jarak jauh. Para pendidik harus diberikan keahlian dan pengetahuan yang cukup untuk bisa mensukseskan program belajar jarak jauh. Tulisan ini akan membahas model pembelajaran yang bisa menjadi rencana alternatif yang bisa digunakan guru untuk meningkatkan prestasi akademik siswa selama masa pandemic Covid-19. Kata-kata kunci: penutupan sekolah, transisi cepat, pembelajaran jarak jauh, model pembelajaran